2003
DOI: 10.1103/physrevb.67.161309
|View full text |Cite
|
Sign up to set email alerts
|

Interband optical transitions in GaP nanowires encapsulated in GaN nanotubes

Abstract: This work investigates the optical properties of cylindrical GaP nanowires encapsulated inside GaN nanotubes (GaP@GaN). Many absorption structures are observed in the range of 2.0-4 eV. Calculations are performed to determine the quantized energy levels of electrons and holes confined in the GaP well. Analytical results indicate that the absorption peaks are attributable to interband optical transitions due to the confined carriers in the heterostructure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For example, 1D nanoscaled materials play an important role in testing and understanding fundamental concepts such as the role of dimensionality and size in optical, electrical, mechanical, and magnetic properties [1][2][3][4][5][6][7][8]. However, the characterization of the physical properties of the 1D nanostructures, in particular from one single nanostructure, has proved to be extremely difficult due to the lack of effective means to manipulate nanoscaled materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 1D nanoscaled materials play an important role in testing and understanding fundamental concepts such as the role of dimensionality and size in optical, electrical, mechanical, and magnetic properties [1][2][3][4][5][6][7][8]. However, the characterization of the physical properties of the 1D nanostructures, in particular from one single nanostructure, has proved to be extremely difficult due to the lack of effective means to manipulate nanoscaled materials.…”
Section: Introductionmentioning
confidence: 99%
“…Despite technological advances in group III-nitride device development, the effects of defects in these materials, mainly due to a lack of native GaN substrates, is an ongoing concern. Recently, however, many epitaxial nanostructures have been reported that are composed of relatively defect-free Ga x Al 1Àx N crystals with nanometer widths, and lengths on the order microns [1][2][3][4][5][6][7][8][9][10]. While these nanocolumns (NCs) take on a variety of aerial densities and the results span a range of growth parameters and epitaxial techniques, a key condition is that NC formation requires epitaxial growth under nitrogen-rich conditions-resulting in reduced Ga surface diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…)) [6][7][8]. At the same time, the 2D/0D semiconductor heterostructure shows hybrid exciton with tuneable binding energy (from 25 to 110 meV) by decreasing the core size of 0D semiconductor [9].…”
Section: Introductionmentioning
confidence: 97%